The engulfment of precipitate by extension twinning in Mg–Al alloy. (November 2020) - Tang, Xiao-Zhi; Guo, Ya-Fang
Abstract: To understand the strengthening mechanism of precipitate against twin-mediated plasticity in magnesium–aluminum alloys, the measurements of the increase in the critical resolved shear stress due to impediment on twin thickening are accomplished based on atomistic simulation, specifically at a significantly low strain rate of 1.7 × 10 6  s −1 . Results show conspicuous coupled effect of temperature and strain-rate on the precipitation strengthening. The strengthening effect vanishes if coherent twin boundary migration is purely stress-driven without thermal activations, due to the back-stress dominating over Orowan stress. At a finite temperature the strengthening effect becomes observable, and is distinctly amplified by high strain rates. Graphical abstract: Image, graphical abstract